Strategies to Achieve Net Zero Emissions 2060 with CSR Disclosure - Andrian, Thomas; Wahyudi, Heru; Leny, Sandra Mei (International Journal of Energy Economics and Policy, 2024)
Intensifying global climate change requires strategic action to reduce negative environmental impacts. One of the key initiatives in the global sustainability agenda is the achievement of Net Zero Emissions by 2060, which is expected to limit global temperature rise and protect ecosystems. In this context, Corporate Social Responsibility (CSR) plays an important role in supporting carbon emission reduction efforts. This study examines the relationship between CSR index and carbon emission reduction through data analysis of energy sector companies in Indonesia. The methods used include content analysis and Pearson correlation test to evaluate the relationship between CSR index scores and carbon emission levels. The results show that an increase in the CSR index score in the environmental category correlates with a decrease in carbon emissions. Effective CSR implementation not only fulfils ethical and legal obligations but also generates a range of strategic benefits for companies, including operational cost savings and reputation enhancement. This study confirms that sustainable CSR strategies can contribute significantly to the achievement of the Net Zero Emissions target by 2060.